PERSESPSI TERHADAP KEPUASAN HIDUP GURU SEKOLAH LANJUTAN - Siti Partini Suardiman (Jurnal Kependidikan, 2000)
This study tried b rtnd  logyakarta oat the degree of teacher life satisfaction and its interactionwith their age, gender, and level of education. Researeh subject of this study were participants of creativity training  teachers. Questionnaire  personal background. It was  for  secondary school was used to reveal the life satisfaction and found  that most of the creativity training alumni of the secondary teachers perceived they had a high life satisfaction rank  from  future. The highest were: psychological satisfaction and in  Independent variables such as age, gender, and level of education turned out only level of education, that has a correlation with life satisfaction. Most of the subject have part time job and that might explain on their solution to the  fact  that teacher's salary is relatively low.